CULTURE AND FOOD POLITICS: UNDERSTANDING FOOD DIVERSITY AND CULTURAL CONFLICTS IN UNIVERSITIES (International Journal of Food and Nutritional Sciences, 2021)
Food is an essential part of human survival. The diversity of food consumption and habits depends on geographical and cultural locations. Human beings eat what they like and what they have for their survival. However, food becomes controversial when people make it sacred and impure. There are politics around making certain foods sacred and others are impure. This food hierarchy creates conflicts among people, it leads to violence and intolerance. The series of incidents in universities indicates cultural conflict over food in university spaces. This cultural conflict is structurally rooted in the very functioning of hegemonic ideology. Hence, democratizing food culture is deeply rooted in counter-cultural politics. Therefore, understanding the dynamics of culture and food politics is important. The present paper outlines the nature and reasons for cultural politics over food with case studies of university incidents. The fieldwork and in-depth interviews with respondents were done at the university.